Clumsiness in fine motor tasks: evidence from the quantitative drawing evaluation of children with Down Syndrome. (28th April 2014) - Vimercati, S. L.; Galli, M.; Stella, G.; Caiazzo, G.; Ancillao, A.; Albertini, G.
Abstract Introduction Drawing tests are commonly used for the clinical evaluation of cognitive capabilities in children with learning disabilities. We analysed quantitatively the drawings of children with Down Syndrome (DS) and of healthy, mental age‐matched controls to characterise the features of fine motor skills in DS during a drawing task, with particular attention to clumsiness, a well‐known feature of DS gross movements. Methods Twenty‐three children with DS and 13 controls hand‐copied the figures of a circle, a cross and a square on a sheet. An optoelectronic system allowed the acquisition of the three‐dimensional track of the drawing. The participants' posture and upper limb movements were analysed as well. Results Results showed that the participants with DS tended to draw faster but with less accuracy than controls. Discussion While clumsiness in gross movements manifests mainly as slow, less efficient movements, it manifests as high velocity and inaccurate movements in fine motor tasks such as drawing.